A biographical account of John Paul Richard Thomas, the man who leaves no stone unturned. Issue 10 (24th March 2021) - Rodríguez‐Robles, Javier A.; Leal, Manuel; Daza, Juan D.; Herrera‐Martínez, Alexandra; Ospina, Oscar E.
Abstract: This biographical account summarizes the professional career and scientific contributions of John Paul Richard Thomas, a contemporary leading figure in the systematics of West Indian amphibians and non‐avian reptiles, especially of blind snakes of the families Typhlopidae and Leptotyphlopidae. Since his first expedition to the West Indies in 1957, Richard's vast field experience (including three trips to Peru between 1968 and 1974), impressive collecting skills, and remarkable ability to detect phenotypic variation among natural populations have resulted in the description of more than 70 species of snakes (24 typhlopids, 4 leptotyphlopids), lizards, and frogs in 16 genera and 11 taxonomic families. Richard joined the faculty of the Department of Biology, University of Puerto Rico, Río Piedras, in 1976 and ever since his efforts significantly advanced organismal biology research at the institution. Although primarily a systematist, his desire to understand multiple aspects of an organism's biology and contagious passion for becoming intimately familiar with animals in their natural environments provided his students the opportunity to conduct research in fields such as behavioral and evolutionary ecology. Richard's mentoring fostered the scientific interests of his graduate students, who were exposed first‐hand to every aspect of research, an invaluable experience that served as a springboard for the development of their professional careers inside and outside academia. This Commentary is a fitting tribute to an influential, unassuming scientist whose passion for turning over rocks has led to the discovery of many interesting species.